Defining and assessing psychological frailty in older adults: a scoping review protocol - Joanes Lameirinhas; Arantxa Gorostiaga; Igone Etxeberria (BMJ Open)
Introduction Frailty is widely acknowledged as a multidimensional construct encompassing physical, psychological and social aspects. However, the lack of consensus in defining and operationalising psychological frailty challenges the holistic approach to frailty advocated by health professionals. Consequently, there is a need to develop a comprehensive definition of psychological frailty based on contributions made by experts in the field, primarily existing frailty assessment tools. This scoping review will aim to identify the key psychological variables that are considered in frailty assessment tools used with older adults as well as to analyse how these psychological variables have been operationalised.Methods and analysis The study will be conducted in accordance with recommendations from several methodological frameworks for scoping reviews and will be reported following Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews statement guidelines. A systematic literature search will be performed in the CINAHL, MEDLINE, PsycInfo, Scopus and Web of Science databases, supplemented by a search in Google Scholar and reference lists. The focus will be on studies that describe the development of multicomponent frailty assessment tools including at least one psychological variable. Study selection and data extraction will be independently conducted by three reviewers working in pairs. Data will be presented in tabular form, and the data will be analysed using qualitative content analysis.Ethics and dissemination This study does not require ethical approval since it is based on secondary data analysis. The findings of the review will be disseminated through publication in a peer-reviewed scientific journal and will be presented at conferences and seminars.Trial registration number The scoping review was registered in Open Science Framework on 29 March 2022 (https://osf.io/bn24y).